Patriarchy and counter discourses: a critique of female subordination in dangarembga's nervous conditions - Kayani, Asma Iqbal; Zahra, Kanwal; Anwar, Behzad (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present study is a critique of an African English novel Nervous Conditions to explore how the writer speaks back to the patriarchal oppression. For this purpose, the researchers intend to explore the patterns of female subordination in African patriarchal society and the ways with which women resist this oppressive system as embedded in Nervous Conditions. The study utilizes Walby's (1990) concept of 'private patriarchy' from his theory of patriarchy. Radical feminism as a feminist perspective of patriarchy provided the theoretical background to carry out this study. Grounded in qualitative research design, the present study utilizes qualitative textual analysis to identify the meaningful patterns working to highlight and challenge patriarchal oppression in the text. The results of the study indicate that the text under study highlights the subordination of African women through seven patterns where they are shown to be a victim of discrimination in the familial domain regarding food distribution, the burden of household work, educational opportunities, daily living conditions, child gender preference, and in freedom of mobility and freedom of opinion/decision. Moreover, the reaction of the women towards this subordination is identified concerning three different aspects where women escape, get entrapped or rebel against this patriarchal system. The study has found Nervous Conditions a challenging narrative that questions the unjust female subordination in a patriarchal society. The researchers conclude the study by substantiating Dangarembga's stance that this game of entrapment, rebellion and escape is disastrous for the females and humanity as a whole.